2007
DOI: 10.1158/0008-5472.can-07-1035
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Tn-MUC1 Glycoform Is Internalized through the Macrophage Galactose-Type C-Type Lectin and Delivered to the HLA Class I and II Compartments in Dendritic Cells

Abstract: The type of interaction between tumor-associated antigens and specialized antigen-presenting cells such as dendritic cells (DCs) is critical for the type of immunity that will be generated. MUC1, a highly O-glycosylated mucin, is overexpressed and aberrantly glycosylated in several tumor histotypes. This results in the expression of tumor-associated glycoforms and in MUC1 carrying the tumor-specific glycan Tn (GalNAcA1-O-Ser/Thr). Glycopeptides corresponding to three tandem repeats of MUC1, enzymatically glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
151
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 49 publications
4
151
0
3
Order By: Relevance
“…The use of synthetic Tn-TAAs for DC targeting represents a promising approach and our model of glycopeptide, MUC1 9Tn , represents here the "proof of concept" of this strategy. We believe and speculate that modifying Tn-density, the length and steric structure of the Tn-peptide, we can possibly obtain immunogens that can efficiently bind to MGL, strongly activate DCs, mimic the effects of a danger signal, and achieve an efficient presentation in HLA class I and II pathways as previously described [18]. Moreover, a wide variety of immunogens carrying Tn-epitopes could be envisaged, where the Tn-peptide stretch could only be a way to deliver other TAAs as well as other molecules.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…The use of synthetic Tn-TAAs for DC targeting represents a promising approach and our model of glycopeptide, MUC1 9Tn , represents here the "proof of concept" of this strategy. We believe and speculate that modifying Tn-density, the length and steric structure of the Tn-peptide, we can possibly obtain immunogens that can efficiently bind to MGL, strongly activate DCs, mimic the effects of a danger signal, and achieve an efficient presentation in HLA class I and II pathways as previously described [18]. Moreover, a wide variety of immunogens carrying Tn-epitopes could be envisaged, where the Tn-peptide stretch could only be a way to deliver other TAAs as well as other molecules.…”
mentioning
confidence: 66%
“…Our previous study, conducted in human setting, demonstrated that the overall structure of Tn-carrying molecules internalized by this receptor highly influenced the antigen processing. In fact, recombinant Tnglycoproteins resembling those shed by tumors remained blocked in HLA class II compartment after internalization, while shorter Tn-antigen formulations were processed in HLA class I and II compartments [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations